Ending nuclear weapons, before they end us - Kamran Abbasi; Parveen Ali; Virginia Barbour; Marion Birch; Inga Blum; Peter Doherty; Andy Haines; Ira Helfand; Richard Horton; Kati Juva; Jose F. Lapena Jr; Robert Mash; et al. (Orapuh Journal, 2025)
A worldwide nuclear arms race is underway. Deployed nuclear weapons are increasing again, and China, India, North Korea, Pakistan, Russia, and the United Kingdom are all enlarging their arsenals. An estimated 2,100 nuclear warheads in France, Russia, the United Kingdom, the United States, and, for the first time, also in China, are on high alert, ready for launch within minutes. With disarmament in reverse, extensive nuclear modernisations underway, multiple arms control treaties abrogated without replacement, no disarmament negotiations in evidence, nuclear-armed Russia and Israel engaged in active wars involving repeated nuclear threats, Russia and the United States deploying nuclear weapons to additional states, and widespread use of cyberwarfare, the risk of nuclear war is widely assessed to be greater than ever. This year, the Doomsday Clock was moved the closest to midnight since the clock's founding in 1947.